Low irradiance multiphoton imaging with alloyed lanthanide nanocrystals - Bining Tian (Nature Portfolio, 2018)
By using a near-IR optical excitation, upconverting nanoparticles may enable high-resolution imaging deep in tissue. Here, Tian et al. introduce alloyed upconverting nanoparticles with improved brightness due to newly described energy transfer pathways.